Mendengar dengan Mata Berkatekese dalam Ecclesia Domestica - Kaluge, Paul (P3TK, Sanata Dharma University, 2020)
This article talks about doing catechesis in ecclesia domestica - Grounded Theorys perspective. Learning the form (Gestalt) of silence in Eastern tradition in terms of Hebraic tradition in the Sacred Scripture, we find out that human-divine interaction in the first Hebrew alphabet of aleph is a simple, relevant and attractive model. Parents can use it in doing catechesis with their kids under five years old. Translanguaging proses in this period requires parents to learn something from their kids. Parents became students of their kids. In this very young age, their kids are the live and the holy text (data). Catechesis Model of Aleph, as we prefer to say it, will be bring the kids to parents, and by doing this the kids will bring the parents to the kids own-selves as well. This catechesis model is a learning model, not a teaching one. Through hearing vision besides seeing voice, the parents as well as the kids will be sensitive enough to distinguish I from me the basic interaction form in every person. However, human-divine interaction represented by aleph is spiritual. In human life experience, is the aleph discovered or invented? Aleph is just an alphabet, but what it points to is really unsayable. As a human-divine interaction, by the way, aleph is the basic model of doing catechesis. This model can inform, perform, and even transform human soul. Parents as well as kids can enter into this human-divine interaction to experience and understand human languaging. The form (Gestalt) is there. It enters, it changes, and it transcendends human life. Hearing vision (mendengar bentuk dalam ruang penglihatan) is a dramatic praxis in daily life.